AB1310 PROSPECTIVE USE OF THE GLUCOCORTICOID TOXICITY INDEX (GTI) IN A COHORT OF VASCULITIS PATIENTS. (June 2019) - Ehlers, Lisa; Wiebe, Edgar; Freier, Desiree; Hermann, Sandra; Miloslavsky, Eli; Zhang, Yuqing; Buttgereit, Frank; Stone, John H.
Abstract : Background: The Charité Rh-GIOP is a prospective study of disease- & bone-related data from patients with chronic inflammatory diseases treated with glucocorticoids (GCs). The Glucocorticoid Toxicity Index app (GTI 2.0) measures changes in GC-associated morbidity. The GTI captures improvement as well as worsening in GC toxicity, and consists of two subscores. With the Cumulative Worsening Score (CWS), only worsening toxicities are counted. The CWS is always a positive number or, if no toxicity has occurred, 0. With the Aggregate Improvement Score (AIS), both improvement and worsening are considered. If the overall GC toxicity has improved, the AIS is negative. Objectives: To evaluate the GTI in a prospective cohort of GC-treated vasculitis patients. Methods: Vasculitis patients were included if starting GC or having a flare requiring increased GC. Doses were calculated in prednisone (PRED) equivalents. Nearly all patients had received GC (often for years) baseline (V1). Data for the 9 GTI domains were collected at V1 and follow-up (V2). These included: medications for hypertension, hyperglycemia, and hyperlipidemia; body mass index; bone mineral density; and data pertaining to muscle strength, skin toxicity, neuropsychiatric effects, and infections. Data for the blood pressure, glucose control, and lipid domains were inferred from treatment changes. We used multivariate logistic regression models to examine the relationship of PRED dose to the likelihood of CWS worsening and AIS improvement. Results: 37 patients (25F; 12M) of mean age 66.6 years (range: 40.5-81.7) were included. Diagnoses: GCA (n=7), PMR (14), AAV (10), EGPA (4), and PAN (2). Thirty-four (92%) patients had changes in GC toxicity between V1-V2. The mean CWS & AIS were 34.8 and 11.1, respectively. Twenty-eight patients (76%) had CWSs >0, indicating worsening toxicity. Twenty-one (57%) had AISs >0, also consistent with overall GC toxicity worsening. However, 13 (35%) had negative AISs, indicating improvements in GC toxicity. BMD measurements worsened by at least 3% in 16 (43%) patients and improved by at least 3% in 9 (24%). Cumulative PRED doses correlated strongly with the CWS. For every 1000mg of PRED between V1 & V2, the risk of CWS increase – worsening of GC toxicity – rose by 79% (Table 2 ). Conclusion: The GTI captured changes in GC toxicity over time well, both improvement and worsening. Cumulative PRED dose correlated strongly with increase in the Cumulative Worsening Score. Acknowledgement: Rh-GIOP is supported by a joint funding of Amgen, Bristol-Meyers Squibb, MS, Celgene, Chugai, Generic Assays, Glaxo-Smith Kline, Hexal AG, Horizon, Lilly, Medac, Mundipharma, Novartis, Pfizer, Roche, and Sanofi. Disclosure of Interests: Lisa Ehlers: None declared, Edgar Wiebe Grant/research support from: Rh-GIOP is supported by a joint funding of Amgen, BMS, Celgene, Generic Assays, Chugai, Hexal AG, Horizon, Lilly, medac, Mundipharma, Novartis, Pfizer, Roche, and Sanofi., Desiree Freier: None declared, Sandra Hermann: None declared, Eli Miloslavsky: None declared, Yuqing Zhang: None declared, Frank Buttgereit: None declared, John H. Stone Grant/research support from: F. Hoffmann-La Roche, Genentech, Xencor, Consultant for: Chugain, F. Hoffmann-La Roche, Genentech, Xencor